Erectile dysfunction drug receipt, risky sexual behavior and sexually transmitted diseases in HIV-infected and HIV-uninfected men. - Cook, Robert L; McGinnis, Kathleen A; Samet, Jeffrey H; Fiellin, David A; Rodriguez-Barradas, Maria C; Rodriquez-Barradas, Maria C; Kraemer, Kevin L; Gibert, Cynthia L; Braithwaite, R Scott; Goulet, Joseph L; Mattocks, Kristin; Crystal, Stephen; et al. (Journal of general internal medicine, 2010)
Health care providers may be concerned that prescribing erectile dysfunction drugs (EDD) will contribute to risky sexual behavior.
Keywords: Adult; Cohort Studies; Cross-Sectional Studies; Drug Prescriptions; Erectile Dysfunction; Follow-Up Studies; HIV Infections; Humans; Male; Middle Aged; Prospective Studies; Sexual Behavior; Sexually Transmitted Diseases; United States; United States Department of Veterans Affairs; Unsafe Sex